The Impact of Carbonated Sodium Bicarbonate Drinks on Physical Fitness in Adolescents - Rahma Badaruddin; Nur A. Salikunna; Moh. Z. Ramadhan; Andi A.M. Tanra; Ikwanul Muslimin (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2023)
Background: Physical fitness is a crucial factor for individuals to support their daily physical activities. Soda beverages have gained popularity among adolescents and are believed to affect physical fitness. Objective: This study investigated the influence of soda consumption on the physical fitness of adolescents. Methods: The study included 30 male participants with 18-25 years old who voluntarily participated and willingly provided informed consent. Physical fitness was measured before and after carbonated sodium bicarbonate drinks consumption using the Harvard Step Test. Participants orally consumed NaHCO3 at a dose of 0.3 gr/kg of body weight in carbonated water at a dose of 0.4 ml/kg of body weight. The employed statistical test was the T-test. Results: The average physical fitness score of the participants before soda consumption was 34.37 ± 13.465, while the average score after soda consumption was 51.57 ± 20.100. The T-test yielded a score of 0.001. Conclusion: Based on the statistical analysis, it can be concluded that carbonated sodium bicarbonate drinks can enhance physical fitness in adolescents.